Adventures in RPL/PLAR/VPL Assessor Training (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
Engaging in RPL (Recognition of Prior Learning), PLAR (Prior Learning Assessment and Recognition) or VPL (Validation of Prior Learning) assessment can be both enlightening and rewarding for assessors, as they often experience deeper insights into assessment and evaluation of learning. Assessors also become more experienced with outcomes-based and competency-based education and the need to meet learners where they are at, and they discover ways to make assessment more meaningful and flexible for learners (Wong, 1999; Thompson & Zakos, 2021). Through our own RPL/PLAR/VPL assessment work, we have found this to be true, as we have experienced similar positive impacts to both our teaching practice and administrative service.  Assessors need support, however, to reap these benefits, often in the form of training and mentorship, as most new assessors have never had to assess work outside of their own courses and classrooms. To facilitate this support, as the recipients of a small innovation grant, we created training modules for new faculty assessors at our Canadian university and uploaded them into our institution's learning management system. The four modules—Introduction to Competency-based PLAR Assessment, Multiple Ways to Assess, From Theory to Practice, and Considering our Biases about Assessment—lead participants through multiple activities about each of those topics. Through the modules, assessor trainees have the opportunity to discuss their own assessment practices with peers and reflect privately on them as well. They are also invited to shadow an experienced assessor team. The training modules culminate in the completion of an assessment of a student competency-based portfolio within a collaborative partnership. By the end of the training, assessors should achieve the following  outcomes:  Explain the difference between experience and learning.  Identify strategies for assessing learning in eight competency areas.  Surface their own biases while conducting assessments.  Assess learning in eight competency areas through student-provided descriptions and evidence of learning.  Reflect on their own learning journey in the area of assessment.  Each module also includes its own learning outcomes that align with the outcomes listed above.  In this workshop, participants had the opportunity to engage in the newly created PLAR Assessor Training modules offered by our Canadian university, including accessing the resources included therein, such as an RPL/PLAR/VPL Assessor Handbook (Forseille et all, 2023). We invited participants to access the course individually or in small  groups, and participants will be able to complete a few brief activities. Participants will be invited to share their own assessor training and practice experiences, including specific learning they have achieved through this work. Attendees will also be invited to share their feedback on the modules.  By the end of the workshop, participants were able to:  Articulate the value of RPL/PLAR/VPL assessment for their own teaching and administrative practices.  Engage in RPL/PLAR assessor training modules.  Reflect on their own assessor learning journeys.  Attendees also left with new tools to enhance their own assessment practices, including not only the modules, but the Assessor Handbook and access to an open-educational resource for learners to help them compose their competency-based RPL/PLAR/VPL portfolios. Keywords: Assessor training, assessment, competency, portfolio